K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

5 tháng 11 2014

2x2-5x-2y2-5y

=2(x2-y2)-5(x+y)

=2(x+y)(x-y)-5(x+y)

=(x+y)(2x-2y-5)

27 tháng 8 2016

a) = 2(x-y)2 - 32 = 2((x-y)2 - 42) = 2(x-y+4)(x-y-4)

b) = 5(x+y)(x-y) -(x-y)= (x-y)( 5(x+y)-1)

24 tháng 8 2017

a, x4 + 2x3 + x\(x^2\left(x^2+2x+1\right)=x^2\left(x+1\right)^2=\left[x\left(x+1\right)\right]^2=\)\(\left(x^2+x\right)^2\)

b, x^3 - x + 3x^2y + 3xy^2+y^3-y

x^3 + 3x^2y + 3xy^2+y^3- x - y

(x+y)^3 - (x+y) 

=(x+y)[ (x+y)^2 - 1]

=(x+y)(x+y+1)(x+y-1)

c, 5x^2 - 10xy + 5y^2 - 20(c hỗ này có dấu gì ko???) z^2 

8 tháng 8 2015

a)x4-1=(x2-1)(x2+1)=(x-1)(x+1)(x2+1)

b)x2-y2-2x+2y=(x-y)(x+y)-2(x-y)=(x-y)(x+y-2)

c)x2-6x-y2+9=(x2-6x+9)-y2=(x-3)2-y2=(x-y-3)(x+y-3)

d)5x2+3(x+y)2-5y2

=5(x2-y2)+3(x+y)2

=5(x-y)(x+y)+3(x+y)2

=(x+y)(5x-5y+3x+3y)

=(x+y)(8x-2y)

26 tháng 7 2015

d)

x3 + 2x2y+ xy2 - 9x 

=x*(x2+2xy+y2 -9)

=x*[ (x+y)2 -3​​] 

=x * (x+y-3) * (x+y-3)

16 tháng 6 2016

x2 - 5x + 5y - y2 =

= -5 (x-y) + (x2 - y2 )

= -5 (x-y) + (x-y)(x+y)

= (x-y) (-5 +x+y)

16 tháng 6 2016

x2-5x+5y-y2

=x2-y2-5x+5y

=(x2-y2)-5(x+y)

=(x2-y2)(-5+x+y)

12 tháng 8 2015

\(x^2-y^2-5x+5y=\left(x^2-y^2\right)-\left(5x-5y\right)\)

                                       \(=\left(x+y\right)\left(x-y\right)-5\cdot\left(x-y\right)\)

                                        \(=\left(x-y\right)\cdot\left[\left(x+y\right)-5\right]=\left(x-y\right)\cdot\left(x+y-5\right)\)

10 tháng 2 2017


a) 5x2 - 10x = 5x( x - 2 )

b) x2 - y2 - 2x + 2y = (x2 - y2) - (2x - 2y)

                             = (x - y ) ( x + y)-2 (x-y)

                             = ( x - y) ( x + y - 2)

c) 4x2 - 4xy - 8y2 = (4x2 - 4xy + 8y2) - 9y2

                           = (2x - 9y2) - 3y2

                           = (2x - y - 3y) (2x - y + 3y)

                           = (2x - 4y) (2x + 2y)

                            = 4(x - 2y) (x + y)

10 tháng 2 2017


a) 5x2 - 10x = 5x( x - 2 )

b) x2 - y2 - 2x + 2y = (x2 - y2) - (2x - 2y)

                             = (x - y ) ( x + y)-2 (x-y)

                             = ( x - y) ( x + y - 2)

c) 4x2 - 4xy - 8y2 = (4x2 - 4xy + 8y2) - 9y2

                           = (2x - 9y2) - 3y2

                           = (2x - y - 3y) (2x - y + 3y)

                           = (2x - 4y) (2x + 2y)

                            = 4(x - 2y) (x + y)

14 tháng 10 2015

\(-x^2+5x+2xy-5y-y^2\)

\(=-x^2+2xy-y^2+5x-5y\)

\(=-\left(x^2-2xy+y^2\right)+\left(5x-5y\right)\)

\(=-\left(x-y\right)^2+5\left(x-y\right)\)

\(=\left(x-y\right).\left[-\left(x-y\right)+5\right]\)

\(=\left(x-y\right).\left(y-x+5\right)\)